Next top villain - Selfors, Suzanne (New York : Little, Brown and Co., 2015)
Unlike her classmates, who include the daughters of Snow White, Cinderella, and Rapunzel, Duchess Swan does not have a Happily Ever After waiting for her, but maybe her class in General Villainy, taught by Mr. Badwolf, can change her destiny.
Booklist, January 2015.
Kirkus Review, November 2014.
Booklist.
Kirkus Review.
6.1
3-6
Keywords: Fairy tales -- Juvenile fiction; Princesses -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Fairy tales -- Fiction; Princesses -- Fiction; Characters in literature -- Fiction; Shapeshifting -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Fantasy; Fairy tales -- Fiction; Princesses -- Fiction; Characters and characteristics in literature -- Fiction; Shapeshifting -- Fiction; Private schools -- Fiction; School stories; Fairy tales -- Fiction; Princesses -- Fiction; Characters in literature -- Fiction; Shapeshifting -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Fantasy fiction